Urban regeneration and mental health: Investigating the effects of an area-based intervention using a modified intention to treat analysis with alternative outcome measures. (January 2020) - Kearns, Ade; Ghosh, Seemanti; Mason, Phil; Egan, Matt
Abstract: A quasi-experimental study of the mental health impacts of regeneration was carried out across fifteen communities in Glasgow, UK, grouped into five and then four types of intervention area. Regression modelling was undertaken to examine the effects of living in each type of area upon mental health (MCS-12 and SF-12 MH) and mental wellbeing (WEMWBS). Living in regeneration areas had no impacts on mental health or wellbeing, possibly due to incomplete implementation. Positive impacts from living in areas of housing improvement were not evident separately for areas of high-rise housing. Areas surrounding regeneration areas exhibited gains in mental health and wellbeing, contrary to notions of negative spillover. Moving between areas had negative effects, especially for those moving beyond the study areas. Changes in mental wellbeing appear less substantial compared with changes in mental health. Highlights: Living in a regeneration area for ten years has no impacts upon mental health. Additional impacts of housing improvements are not found in high-rise estates. In adjacent areas with social change, there are positive impacts on mental health. Moving to non-treatment areas further away has a negative effect on mental health. Impacts on mental wellbeing are less sizeable than effects on mental health.